Effect of Cryopreservation on Functional Status of Bone Marrow Hematopoietic and Mesenchymal Stem Cells in Animals with Autoimmune Pathology - Goltsev, Anatoliy N.; Gayevskaya, Yuliya A.; Dubrava, Tatyana G.; Ostankova, Lyudmila V. (Problems of Cryobiology and Cryomedicine, 2016)
The application of cryopreserved autologous bone marrow (BM) is the reconstructive therapy tool for autoimmune diseases (AIDs). The BM use efficiency is determined by preservation rate of its hematopoietic and mesenchymal stem cells (HSCs and MSCs, respectively). This fact determines the need to design the optimal cryopreservation regimens for the BM of AIDs donors. Here we assessed a functional status of bone marrow HSCs and MSCs of mice with adjuvant arthritis (AA), initiated by Freund’s complete adjuvant administration. The bone marrow of CBA/H mice to day 14 of AA (chronic stage) and that of healthy animals were cryopreserved under dimethyl sulfoxide protection. The content of HSCs of various differentiation extent was determined by spleen colony formation in vivo to days 8 (CFU-S-8) and 14 (CFU-S-14). Functional activity of MSCs in BM was studied in vitro by the content of fibroblast colony forming units (CFU-F). There was established the fact of altering the functional potential of hematopoietic progenitor cells of BM of various differentiation levels (CFU-S-8, CFU-S-14) and their stromal microenvironment (CFU-F) during clinical manifestation of AA. After cryopreservation of AA animals’ BM cells with 7% DMSO a functional potential of CFU-S and CFU-F was established to be similar to the healthy animals’ BM, cryopreserved with 10% DMSO. The cryopreserved with the proposed regimen autologous BM may be used for a targeted recovery of lymphohemopoietic system in AA animals. Probl Cryobiol Cryomed 2016; 26(1):63-72.